Prevention of Tooth Discoloration Using Fluoride Varnish Immediately After Bleaching - Ryotaro Yago; Chiharu Kawamoto; Rafiqul Islam; Hirofumi Kaneko; Monica Yamauti; Masayuki Otsuki; Hidehiko Sano; Atsushi Tomokiyo (Journal of Functional Biomaterials)
Tooth bleaching is a widely used esthetic treatment; however, bleaching agents can temporarily alter the surface morphology of enamel, increasing surface roughness and porosity, which may lead to increased susceptibility to discoloration. This in vitro study investigated the effectiveness of fluoride varnish in preventing immediate discoloration of bovine incisors after bleaching. Specimens were bleached with 35% hydrogen peroxide and treated with either Clinpro White Varnish (CW) or Enamelast Fluoride Varnish (EN), whereas control specimens received no treatment after bleaching. The samples were immersed in coffee for 24 h, and the color difference (ΔE00) was calculated using the CIEDE2000 formula. The surface morphology of enamel was examined using SEM. The fluoride varnish groups showed significantly lower color difference values than the control group (p < 0.05), with ΔE00 reduced by approximately two-thirds in both the CW and EN groups. SEM observations showed that the enamel surfaces in the varnish-treated groups exhibited reduced surface irregularities compared to the untreated group, suggesting remineralization. These results suggest that the immediate application of fluoride varnish after bleaching can effectively reduce short-term discoloration by providing physical protection and promoting remineralization. Fluoride varnish may serve as a simple and effective strategy to maintain whitening outcomes and minimize early discoloration.